Millionaires for the month - McAnulty, Stacy (Yearling, 2022)
Seventh graders Benji and Felix learn life lessons about money after they "borrow" twenty dollars from a wallet they find while on a field trip, as the billionaire owner challenges them to spend over five million dollars in thirty days.